1987
DOI: 10.1161/01.cir.76.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Conduction over an isthmus of atrial myocardium in vivo: a possible model of Wolff-Parkinson-White syndrome.

Abstract: Antiarrhythmic drugs appear preferentially to prolong refractoriness of accessory pathways compared with atrial or ventricular muscle in patients with the Wolff-Parkinson-White syndrome. This response may be due to intrinsic properties of accessory pathways or to depressed conduction associated with a narrow strip, or isthmus, of tissue. To test the latter possibility, in 16 anesthetized dogs we surgically isolated a portion of the right atrial myocardium in the form of an ellipse (10 to 25 x 8 to 15 mm). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…There were no significant differences between intra-atrial delay in looped hearts properties, the myocardium of the atrioventricular canal differs from atrial or ventricular myocardium in its ability to induc e endocardial cushion formation (9) and in its ultimate fate, which is to be replaced by the fibrous tissue of the atrio ventri cular ring. It is tempting to speculate that accessory atrioventricular connections, which more often exhibit electrophysiologic characteristics of working myocardium than of atrioventricular node (10,11), have their origin in strands of atrioventricular canal myocardium that fail to electrophysiologically different iate from adjacent myocardium and that subsequently fail to yield their position to fibrous connective tissue.…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences between intra-atrial delay in looped hearts properties, the myocardium of the atrioventricular canal differs from atrial or ventricular myocardium in its ability to induc e endocardial cushion formation (9) and in its ultimate fate, which is to be replaced by the fibrous tissue of the atrio ventri cular ring. It is tempting to speculate that accessory atrioventricular connections, which more often exhibit electrophysiologic characteristics of working myocardium than of atrioventricular node (10,11), have their origin in strands of atrioventricular canal myocardium that fail to electrophysiologically different iate from adjacent myocardium and that subsequently fail to yield their position to fibrous connective tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature claimed that anatomical structural differences in and near the APs apparently affected refractoriness and conduction properties of the APs [20]. Branching of the manifest APs might be the anatomical substrate responsible for micro-reentry and reflection [18].…”
Section: Discussionmentioning
confidence: 96%
“…Inoue et al 15 and Abe et al 16 have already reported that an artificial isthmus on the canine right atrium caused conduction blocks or slowing of conduction, but it was not reproducible and the conduction property of the isthmus was not fully evaluated. In our preliminary studies, conduction in the isthmus was not reproducible when the isthmus was made between 2 linearly ablated areas on the right atrium, probably because of the rough and irregular edge of the ablated areas.…”
Section: Discussionmentioning
confidence: 99%